На заставе: стихи / Агния Барто; рисунки И. Година - Барто Агния Львовна (Мои первые книжки, 1983)
Экземпляры: ДО (20190409) / Инвентарный номер: zzzzz / Цена: 3.00 / Авт.знак: Б 26 / ГРНТИ: 17.82 / ББК: 84(2 Рос=Рус)6